Clinical and echocardiographic characteristics associated with the development of infective endocarditis in patients with significant mitral stenosis. Issue 1 (20th December 2021) - Ngiam, Jinghao Nicholas; Chew, Nicholas WS; Sim, Meng Ying; Liong, Tze Sian; Li, Tony Yi‐Wei; Leow, Ryan; Sia, Ching‐Hui; Loh, Poay Huan; Wong, Raymond CC; Yeo, Tiong‐Cheng; Poh, Kian Keong; Kong, William KF
Abstract: Background: : Infective endocarditis (IE) confers significant mortality and morbidity in patients with underlying mitral stenosis (MS), with both diseased native valves and after valvular procedures. Purpose: : We examined the clinical and echocardiographic parameters in association with the development of IE on patients with significant MS. Methods: : A total of 478 consecutive patients with index echocardiographic diagnosis of significant mitral stenosis (mitral valve area <1.5 cm 2 ) were included. Patients were grouped into those with or without IE on at least 5 years of follow‐up. Baseline clinical, echocardiographic profile and clinical outcomes were compared. Results: : IE was observed in 4.4% ( n = 21) of the cohort. These patients were younger (45.3 ± 14.6 vs. 53.2 ± 15.5 years, p = 0.022) at the time of MS diagnosis. NT‐proBNP was higher in patients who developed IE (13529 ± 12230 vs. 4381 ± 5875 pg/ml, p < 0.001), with larger left atrial diameter (54.4 ± 10.1 vs. 49.9 ± 9.5 mm, p = 0.040) and elevated pulmonary artery systolic pressure (PASP, 62.3 ± 17.2 vs. 47.2 ± 16.5 mmHg, p = 0.026). There was no significant difference in terms of MS severity, other concomitant valvulopathies, or etiology (rheumatic or degenerative) of MS. Patients who smoked had higher incidence of IE (33.3% vs. 14.2%, log‐rank 7.27, p = 0.007). After adjusting for age, valve procedure and PASP, patients who smoked remained at elevated risk of IE (adjusted hazards ratio 2.99, 95% confidence interval 1.18–7.56, p = 0.021). Conclusion: : IE occurs in a proportion of patients with MS. Smoking, younger age of diagnosis of MS as well as dilated left atria with elevated PASP may be associated with an elevated risk of this complication.